Genetic Polymorphism In Individuals With Type II Diabetes Mellitus Using PCR-RAPD In Sidoarjo District - Miftahul Mushlih; Fitri Kumala Sari; Djauharoh A. Hadie; Syahrul Ardiansyah (Jurnal Ilmiah Kesehatan, 2021)
Diabetes Mellitus type II (DMT2) is a metabolic disorder which its number increases from year to year. The Control of DMT2 sufferer’s number is difficult because DMT2 is caused by genetic and environmental factors. DMT2 can worsen infectious diseases for people with other infectious diseases. This study aimed to determine the polymorphism of sufferers and non-sufferers of T2DM using PCR-RAPD method. The sample of this study consisted of 60 samples which 30 positive samples and 30 negative samples taken from several clinics in Sidoarjo district. The primer used is A 18 (5'- AGGTGACCGT-3 '). Data analysis was performed using the SPSS 16.00 program and analyzed with a Cross-sectional Chi-square with a 95% confidence level. The results of this study produced 17 bands with length of 197 bp, 239 bp, 269 bp, 319 bp, 390 bp, 530 bp, 588 bp, 686 bp, 777 bp, 972 bp, 1175 bp, 1676 bp, 2780 bp, 3843 bp, 6563 bp, 11072 bp & 18434 bp. Four of them were monomorphic and two bands showed significantly different results at 319 bp (p: 0.035) and 18434 bp (p: 0.004).there were significant differences in the resulting band at 319 (p: 0.035) bp and 18434 bp (p: 0.004). Further analysis needs to be done to confirm the genes involved.